2017
DOI: 10.1371/journal.pone.0186645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the first knock-out aldh7a1 zebrafish model for pyridoxine-dependent epilepsy using CRISPR-Cas9 technology

Abstract: Pyridoxine dependent epilepsy (PDE) is caused by likely pathogenic variants in ALDH7A1 (PDE-ALDH7A1) and inherited autosomal recessively. Neurotoxic alpha-amino adipic semialdehyde (alpha-AASA), piperideine 6-carboxylate and pipecolic acid accumulate in body fluids. Neonatal or infantile onset seizures refractory to anti-epileptic medications are clinical features. Treatment with pyridoxine, arginine and lysine-restricted diet does not normalize neurodevelopmental outcome or accumulation of neurotoxic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In the last decade, zebrafish (Danio rerio) has emerged as a new, attractive species for modeling human brain disorders. With regard to epilepsy research, the utility of zebrafish to mimic aspects of this human disorder has been demonstrated for Dravet syndrome (i.e., SCN1A mutations) [22,23], pyridoxine-dependent epilepsy (ALDH7A1 and PLPBP) [24,25], focal seizures (DEPDC5) [26], or in CHD2-mediated epileptic encephalopathies [27,28]. More recently, Samarut et al [29], using CRISPR/Cas9 technology, generated a new gabra1 −/− mutant zebrafish line in order to unravel the epileptogenic mechanisms underlying gabra1 deficiency and this study undoubtedly confirmed the potential of zebrafish for elucidating mechanisms underlying the process of epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, zebrafish (Danio rerio) has emerged as a new, attractive species for modeling human brain disorders. With regard to epilepsy research, the utility of zebrafish to mimic aspects of this human disorder has been demonstrated for Dravet syndrome (i.e., SCN1A mutations) [22,23], pyridoxine-dependent epilepsy (ALDH7A1 and PLPBP) [24,25], focal seizures (DEPDC5) [26], or in CHD2-mediated epileptic encephalopathies [27,28]. More recently, Samarut et al [29], using CRISPR/Cas9 technology, generated a new gabra1 −/− mutant zebrafish line in order to unravel the epileptogenic mechanisms underlying gabra1 deficiency and this study undoubtedly confirmed the potential of zebrafish for elucidating mechanisms underlying the process of epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR technology has provided avenues for engineering of cells, tissues, and whole organisms across the biological spectrum. Aside from the amazing potential for gene editing as a diagnostic tool and perhaps even a treatment for many debilitating diseases (Ortiz-Virumbrales et al 2017;Reczek et al 2017;Zabinyakov et al 2017), the potential possible uses of this technology in plants and livestock animals is similarly impressive (Lamas-Toranzo et al 2017). Creation of disease-resistant and less allergenic food crops (Hummel et al 2018;García-Molina et al 2019) with enhanced nutrient profiles (Wang et al 2019) is now within our reach; the future implications for feeding a progressively larger world population are immense.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, two independent groups reported that the zebrafish aldh7a1 null mutant recapitulates the characteristics of pyridoxine-dependent epilepsy (PDE) caused by variants of the gene ALDH7A1 [ 82 , 96 ]. Two homozygous mutants were generated using CRISPR/Cas9.…”
Section: Crispr Applications In Neural Diseasesmentioning
confidence: 99%
“…In the first, a 5-bp deletion mutant in the zebrafish aldh7a1 gene resulted in a premature stop codon; in the second, a 5-nucleotide insertion introduced a stop codon at position 50 of the translated protein sequence. In both studies, the mutants showed a spontaneous rapid increase in locomotion and a rapid circling swim behavior followed by seizure-like locomotor behaviors as early as 8 dpf [ 96 ] or 10 dpf [ 82 ], which resulted in death shortly after a seizure. Also, electroencephalographic recordings revealed large-amplitude spike discharges.…”
Section: Crispr Applications In Neural Diseasesmentioning
confidence: 99%